Pengaruh Budaya Organisasi, Kepuasan Kerja, dan Motivasi Kerja Guru Terhadap Kinerja Guru Sekolah Dasar Negeri - Wusqo, Urwatul; Wuryandini, Endang; Rasiman, Rasiman (Persatuan Guru Republik Indonesia Kota Semarang, 2023)
The background of this research is related to the performance of state elementary school teachers in Larangan District, Brebes Regency in preparing learning administration, implementation and evaluation which has not been optimal as an organizational culture in the school. Low levels of job satisfaction due to job dissatisfaction and discomfort with the work atmosphere as well as low work motivation cause problems with teacher performance. Based on this background, research was carried out to analyze the influence of organizational culture, job satisfaction and motivation of state elementary school teachers in Larangan District, Brebes Regency. This research aims to examine and analyze: (1) the influence of organizational culture on the performance of elementary school teachers, (2) the influence of job satisfaction on the performance of elementary school teachers, (3) the influence of work motivation on the performance of elementary school teachers, and (4) the simultaneous influence of organizational culture , job satisfaction, and teacher work motivation on elementary school teacher performance. This research method is descriptive quantitative. The research population was 385 people, the sample was 193 people. The data collection method uses a questionnaire method. The instrument test used is the validity and reliability test. The classical assumption test uses the normality test, linearity test, multicollinearity test, and homogeneity test. Data analysis used simple linear regression test, multiple linear regression test, F test (ANOVA) and t test. Based on the research results, it can be concluded as follows: (1) Organizational culture has a positive and significant effect on the performance of state elementary school teachers in Larangan District, Brebes Regency, it is proven that t count is 48.454 > t table 1.97. The magnitude of the influence of organizational culture variables on teacher performance variables is 92.5%; (2) Job satisfaction has a positive and significant effect on the performance of state elementary school teachers in Larangan District, Brebes Regency. It is proven that t count is 31,500 > t table 1.97. The magnitude of the influence of the job satisfaction variable on the teacher performance variable is 83.90%; (3) work motivation has a positive and significant effect on the performance of state elementary school teachers in Larangan District, Brebes Regency. It is proven that t count is .766 > t table 1.97. The magnitude of the influence of the work motivation variable on the teacher performance variable is 85.50%; (4) Organizational culture, job satisfaction and teacher work motivation have a positive and significant effect on the performance of public elementary school teachers in Larangan District, Brebes Regency, as proven by the calculated F value of 814.606 > F table 2.650 with a significance level of 0.000 < 0.05. Simultaneous influence of 92.8%. The suggestions put forward by researchers are: (1) To improve teacher performance, it is best for leaders, in this case the Principal, to always motivate teachers to work by providing opportunities to carry out social activities and directing teachers to always maintain good relationships with other teachers; (2) The school principal always provides encouragement and good practices for teachers so that they are always consistent in building the school's organizational culture and motivates teachers to always innovate both in learning and in exploring the details of their work duties; (3) To increase job satisfaction, school principals are expected to provide appreciation for the results of teachers' performance. Key words: organizational culture, job satisfaction, work motivation, teacher performance.